Harga, Merek dan Kualitas Motor Bekas Terhadap Keputusan Pembelian Showroom Jawa Motor - Rizky, Anang Rizky Nugraha; Zakiyah Zahara; Syamsul Bahri Dg. Parani; Sri Wanti (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the influence of price, brand, and product quality on consumer purchasing decisions at the Jawa Motor Showroom in Palu City.. Methodology/approach: Using a quantitative approach, data were collected through a questionnaire involving 120 respondents who had purchased used motorcycles at a showroom. The testing in this study used multiple linear regression analysis using the SPSS application. Results/findings: The study found that price, brand image, and product quality significantly influenced consumer purchasing decisions. Competitive pricing attracts cost-conscious buyers, a strong brand enhances trust and perceived value, and high product quality assures satisfaction. Together, these factors explain 86.4% of the variance in consumer decisions, highlighting their dominant role in shaping purchasing behaviors. Conclusions: Businesses that offer competitive pricing, maintain a strong brand reputation, and ensure product quality are more likely to influence consumer purchase decisions. Limitations: The study was limited to one used motorcycle showroom, namely the Jawa Motor Showroom in Palu City; therefore, the results cannot be generalized to other used motorcycle showrooms in Palu City. Contribution: This study contributes to the development of effective marketing strategies for business actors in the field of used motorcycle sales.